Females Are Protected From Iron‐Overload Cardiomyopathy Independent of Iron Metabolism: Key Role of Oxidative Stress. Issue 1 (23rd January 2017) - Das, Subhash K.; Patel, Vaibhav B.; Basu, Ratnadeep; Wang, Wang; DesAulniers, Jessica; Kassiri, Zamaneh; Oudit, Gavin Y.
Abstract : Background: Sex‐related differences in cardiac function and iron metabolism exist in humans and experimental animals. Male patients and preclinical animal models are more susceptible to cardiomyopathies and heart failure. However, whether similar differences are seen in iron‐overload cardiomyopathy is poorly understood. Methods and Results: Male and female wild‐type and hemojuvelin‐null mice were injected and fed with a high‐iron diet, respectively, to develop secondary iron overload and genetic hemochromatosis. Female mice were completely protected from iron‐overload cardiomyopathy, whereas iron overload resulted in marked diastolic dysfunction in male iron‐overloaded mice based on echocardiographic and invasive pressure‐volume analyses. Female mice demonstrated a marked suppression of iron‐mediated oxidative stress and a lack of myocardial fibrosis despite an equivalent degree of myocardial iron deposition. Ovariectomized female mice with iron overload exhibited essential pathophysiological features of iron‐overload cardiomyopathy showing distinct diastolic and systolic dysfunction, severe myocardial fibrosis, increased myocardial oxidative stress, and increased expression of cardiac disease markers. Ovariectomy prevented iron‐induced upregulation of ferritin, decreased myocardial SERCA2a levels, and increased NCX1 levels. 17β‐Estradiol therapy rescued the iron‐overload cardiomyopathy in male wild‐type mice. The responses in wild‐type and hemojuvelin‐null female mice were remarkably similar, highlighting a conserved mechanism of sex‐dependent protection from iron‐overload‐mediated cardiac injury. Conclusions: Male and female mice respond differently to iron‐overload‐mediated effects on heart structure and function, and females are markedly protected from iron‐overload cardiomyopathy. Ovariectomy in female mice exacerbated iron‐induced myocardial injury and precipitated severe cardiac dysfunction during iron‐overload conditions, whereas 17β‐estradiol therapy was protective in male iron‐overloaded mice.